(3TQM cdjGJ GdbGfhf aj GdWH dGHf SjfGs - (3bWH GdOjf , eMehO Hf eSYhO GdTjQGRis; (3GdQFjS GHf SjfG , CHh Ydj TQa Gdedc (B: (3GdajdSha GdQFjS,J (B428 (3g` s ((3eMeO Hf Ydi s)
(3ChdgG (B:s
(3CeG HYO aEf eMehO Hf eSYhO GHf eUdM GdTjQGRi , jbhd (B: (3deG cGf CYRH eTGQH GdfYe s
(3BNQgG (B:s
(3dYdg jLO eNQLkG UGdMkG dh Obb GdfXQ hefgLkG hGVMkG dhdGMX GdebUO GdeYJHQ s
(3bWYI JHOC HChd GdTQMs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs